2015
DOI: 10.3402/ijch.v74.29256
|View full text |Cite
|
Sign up to set email alerts
|

Lower respiratory tract infection hospitalizations among American Indian/Alaska Native children and the general United States child population

Abstract: BackgroundThe lower respiratory tract infection (LRTI)-associated hospitalization rate in American Indian and Alaska Native (AI/AN) children aged <5 years declined during 1998–2008, yet remained 1.6 times higher than the general US child population in 2006–2008.PurposeDescribe the change in LRTI-associated hospitalization rates for AI/AN children and for the general US child population aged <5 years.MethodsA retrospective analysis of hospitalizations with discharge ICD-9-CM codes for LRTI for AI/AN children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 36 publications
2
63
2
Order By: Relevance
“…The rate of LRTI-associated hospitalizations is >4 times higher in children less than 1 year of age compared to those between 1 and 4 years (1) and infants younger than 6 months of age are particularly vulnerable to the development of severe disease (2). Not surprisingly then, the highest risk of death occurs in the first years of life (2).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of LRTI-associated hospitalizations is >4 times higher in children less than 1 year of age compared to those between 1 and 4 years (1) and infants younger than 6 months of age are particularly vulnerable to the development of severe disease (2). Not surprisingly then, the highest risk of death occurs in the first years of life (2).…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies show that childhood pneumonia is associated with asthma, and with impaired lung function, which persists into adulthood [21]. The study region has one of the highest LRTI hospitalisation rates in the US [1,22], with median cost of LRTI hospitalisation for respiratory syncytial virus estimated at $22,323 [23]. One out of 63 children in this region develop a chronic lung condition, bronchiectasis, from severe or repeated pneumonias, which can lead to increased morbidity in adulthood [2,24].…”
Section: Discussionmentioning
confidence: 99%
“…Alaska Native children living in rural southwest Alaska experience some of the highest reported rates of hospitalisation from lower respiratory tract infections (LRTIs) [1]. The pneumonia hospitalisation rate for infants from Alaska’s southwest Yukon Kuskokwim (YK) Delta region is tenfold higher than for other US infants [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Population-based studies in the US and Australia have shown substantially higher rates of hospital admissions (an indicator of severe infant morbidities) in Indigenous than in non-Indigenous infants. [8][9][10][11][12][13][14] Likewise, we would expect substantial disparities in Indigenous versus non-Indigenous infant hospitalizations in Canada. Indigenous infants in Canada often live in communities with poor access to high-quality care, and in communities and families with poor socioeconomic conditions that are strongly predictive of poor infant health.…”
mentioning
confidence: 99%